Fuel injection system / Muhamad Shah Osmin ... [et al.] - Osmin, Muhamad Shah; Hashim, Muhammad Fahmi; Abd. Kadir, Mohd Zulharis; Abu Hassan, Mohamed Heszzuddin (2001)
In completing our final project's report we've done our research for the last 12 months. We've done a research on the fuel injection system. Now we know what are the different between an electronic fuel-injection system and a diesel fuel-injection system. We've done the research to improve our knowledge and it really helps us to understand the fuel-injection system very well. We also able to diagnose if the engine got any problem. We were also able to know what the advantages and the disadvantages between both system. The conclusion that we made is that if you want a vehicle with a power output, you should use a diesel engine, but if you want a vehicle that is environmentally friendly, you should get a gasoline engine.